The Anesthesiologist's Perspective Regarding Non-intubated Thoracic Surgery: A Scoping Review - Rosboch, Giulio Luca; Lyberis, Paraskevas; Ceraolo, Edoardo; Balzani, Eleonora; Cedrone, Martina; Piccioni, Federico; Ruffini, Enrico; Brazzi, Luca; Guerrera, Francesco (Frontiers in Surgery, 2022)
Non-intubated thoracic surgery (NITS) is a growing practice, alongside minimally invasive thoracic surgery. To date, only a consensus of experts provided opinions on NITS leaving a number of questions unresolved. We then conducted a scoping review to clarify the state of the art regarding NITS. The systematic review of all randomized and nonrandomized clinical trials dealing with NITS, based on Pubmed, EMBASE, and Scopus, retrieved 665 articles. After the exclusion of ineligible studies, 53 were assessed examining: study type, Country of origin, surgical procedure, age, body mass index, American Society of Anesthesiologist’s physical status, airway management device, conversion to orotracheal intubation and pulmonary complications rates and length of hospital stay. It emerged that NITS is a procedure performed predominantly in Asia, and certain European Countries. In China, NITS is more frequently performed for parenchymal resection surgery, whereas in Europe, it is mainly employed for pleural pathologies. The most commonly used device for airway management is the laryngeal mask. The conversion rate to orotracheal intubation is approximately 3%. The results of the scoping review seem to suggest that NITS procedures are becoming increasingly popular, but its role needs to be better defined. Further randomized clinical trials are needed to better define the role of the clinical variables possibly impacting on the technique effectiveness.